(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
This paper explores the synthesis and comprehensive characterization of magnesium oxide-doped iron (III) oxide nanoparticles (MgO-Fe2O3 NPs). Utilizing a modified sol-gel method, the study focused on integrating MgO and Fe2O3 to harness the synergistic effects of both metal oxides. The characterization techniques used include X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy, UV-Vis spectroscopy, and Field Emission Scanning Electron Microscopy (FE-SEM), accompanied by Energy-dispersive X-ray Spectroscopy (EDX). Key findings from XRD analysis demonstrated a well-crystallized material with a range of crystallite sizes, calculated using the Scherrer formula, with an average size of 18.82 nm. FT-IR spectra identified several bonding interactions indicative of MgO and Fe2O3 phases, with specific peaks at 418, 549, and 1155 corresponding to metal-oxygen bonds and interactions. UV-V is absorbance measurements revealed a significant peak at 225 nm with a sharp decrease in absorbance at wavelengths above 300 nm, suggesting effective UV light absorption, which is critical for potential photocatalytic applications. The band gap estimated from Tauc plots was approximately 3 eV, confirming the material's suitability as a wide band gap semiconductor. The FE-SEM images indicated that the nanoparticles were spherical, with an average diameter of about 30 nm. This implies a uniform distribution and high surface area to volume ratio, which is indispensable for enhanced reactivity. EDX evidenced the composition of the nanoparticles, and the iron, magnesium, and oxygen peaks obviously doped the Fe2O3 into the MgO matrix. The synthesis of MgO-Fe2O3 nanoparticle sensors based on this novel sol-gel method opens an avenue to develop efficient sensors.